Orientações para a disseminação de achados científicos para profissionais da engenharia de software - Neris, Adalberto Pereira (2024)
Context: The Software Engineering (SE) community has strived to generate evidence about the best tools, methods, and strategies to be adopted in practice. However, much of the published research in ES has minimal impact on industrial practice, and its full potential benefits are not being realized. Gap: One of the barriers between the discovery of knowledge in SE and its application in industry is ineffective dissemination, arising from the lack of specific guidance on the audience, message, communication channels, and tools for disseminating scientific findings for SE practitioners. Objective: Therefore, this work discusses insights on disseminating academic research findings to SE professionals. Method: Initially, after the development of an interview script, semi-structured interviews were conducted to identify, from the industry’s perspective, aspects related to the dissemination of scientific findings such as audience, message, and communication channels. The interviews were transcribed and coded. The knowledge derived from these activities was crucial in defining the proposed guidelines. Results: Interviewees expressed the need to align academic research with industry needs and diversify communication formats and channels, including open platforms and social networks as elements to promote the dissemination, accessibility, and clarity of scientific knowledge. Conclusion: In addition to the interaction between academia and industry, the insights are expected to contribute to developers’ decisions about technologies being based on evidence